FAKTOR PENDORONG PERTUMBUHAN EKONOMI DAERAH DI INDONESIA - Agus Tri Basuki (Universitas Pembangunan Nasional Veteran Yogyakarta, 2020)
This study aims to examine the role of fiscal policy and macro variables in encouraging regional economic growth in Indonesia. This study uses panel data regression using a sample of 18 provinces in Indonesia. Research supporting data sourced from the Indonesian Central Bureau of Statistics and the Ministry of Financeof the Republic of Indonesia from 2008-2017. The results showed that local government spending on education, health, agriculture, and fisheries and maritime affairs had a positive effect on economic growth, but the effect was less effective in promoting economic growth. To overcome the ineffective role of fiscal policy in promoting economic growth, the central and regional governments must change budgeting from a traditional approach to a budgeting approach to performance. Based on the regional financial management law, regional leaders have power over regional budget management, but in the use of the budget it must be used for the maximum welfare of the people. Meanwhile, the role of foreign investment in promoting economic growth is very low. The government's role in overcoming the low role of foreign investment is only to provide business permits for pro-laborintensive foreign investment.Penelitian ini bertujuan untuk menguji peran kebijakan fiskal dan variabel makro dalam mendorong pertumbuhan ekonomi daerah di Indonesia. Penelitian ini menggunakan regresi data panel dengan menggunakan sampel dari 18 provinsi di Indonesia. Data pendukung penelitian bersumber dari Badan Pusat Statistik Indonesia dan Kementerian Keuangan Republik Indonesia tahun 2008-2017. Hasil penelitian menunjukkan bahwa belanja pemerintah daerah untuk pendidikan, kesehatan, pertanian, serta perikanan dan kelautan berpengaruh positif terhadap pertumbuhan ekonomi, namun pengaruhnya kurang efektif dalam mendorong pertumbuhan ekonomi. Untuk mengatasi tidak efektifnya peran kebijakan fiskal dalam mendorong pertumbuhan ekonomi, pemerintah pusat dan daerah harus mengubah penganggaran dari pendekatan tradisional menjadi pendekatan penganggaran menuju kinerja. Berdasarkan undang-undang pengelolaan keuangan daerah, pemimpin daerah memiliki kewenangan atas pengelolaan anggaran daerah, namun dalam penggunaan anggarannya harus digunakan untuk sebesar-besar kemakmuran rakyat. Sedangkan peran investasi asing dalam mendorong pertumbuhan ekonomi sangat rendah. Peran pemerintah dalam mengatasi rendahnya peran penanaman modal asing hanya memberikan izin usaha bagi penanaman modal asing yang pro padat karya.